Minocycline suppresses disease-associated microglia (DAM) in a model of photoreceptor cell degeneration - Doyle, Sarah; Campbell, Matthew (My University, 2022)
As the resident immune cells in the retina, microglia play important homeostatic roles in retinal immune regulation and neuroprotection. However, chronic microglia activation is a common hallmark of many degenerative retinal diseases. The semi-synthetic tetracycline antibiotic, minocycline, appears to inhibit pro-inflammatory microglia which coincides with protection against photoreceptor cell degeneration. A sub-type of microglia termed disease associated microglia (DAM) have recently been associated with a wide range of central nervous system (CNS) diseases. In this study we examine the kinetics of microglia infiltration towards the outer retina of rhodopsin knockout mice (Rho−/−) by immunofluorescence, and undertake transcriptional and spatial localization analysis of markers for evidence of both homeostatic function and appearance of DAM. We demonstrate in the Rho−/− mice, IBA1+ and P2RY12+ microglia take on an activated morphology early in disease, prior to notable photoreceptor loss and are capable of infiltrating the subretinal space. Expression of lipid processing enzyme and DAM-marker lipoprotein lipase (LPL) is primarily observed only after microglia have traversed the ONL. Administration of minocycline to Rho−/− mice induced loss of phagocytic/DAM microglia in the outer retina in vivo coinciding with photoreceptor survival and amelioration of retinal degeneration. Overall, we show that minocycline suppresses many DAM markers, in particular those associated with lipid metabolism indicating that suppression of this process is one mechanism by which minocycline protects against inflammation induced photoreceptor cell death.
PUBLISHED
cited By 1
Keywords: CELL DEATH; retina; microglia; CELL DEATH; retina; microglia